2017
DOI: 10.1177/0255761417689920
|View full text |Cite
|
Sign up to set email alerts
|

Music in preschool class: A quantitative study of factors that determine the extent of music in daily work in Swedish preschool classes

Abstract: The aim of this article is to highlight what opportunities a six year old in preschool class in Sweden might have for participating in and being inspired by music. We ask the following question: What factors determine how music teaching is conceived and carried out in preschool class? The present study is quantitative in character, and data were collected by means of a survey sent out to all teachers working with preschool classes in a Swedish city. We have brought a hermeneutic approach to bear on our compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
(41 reference statements)
1
10
0
4
Order By: Relevance
“…Barrett et al (2019) found that the more qualified the ECEC staff members were (that is, the more training they had as ECEC teachers), the less favourable their beliefs regarding the role of music in ECEC settings. Ehrlin and Tivenius (2018) reported similar findings; ECEC staff members who mainly see music as something important in and of itself (l'art pour l'art) carry out fewer music activities than peers who value music's transfer effects. The reason for this, argue Ehrlin and Tivenius, is if music is important in itself, it must be difficult to do, but if music is for learning about colours or the days of the week, singing is an appropriate activity because the students are not performing 'real music.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Barrett et al (2019) found that the more qualified the ECEC staff members were (that is, the more training they had as ECEC teachers), the less favourable their beliefs regarding the role of music in ECEC settings. Ehrlin and Tivenius (2018) reported similar findings; ECEC staff members who mainly see music as something important in and of itself (l'art pour l'art) carry out fewer music activities than peers who value music's transfer effects. The reason for this, argue Ehrlin and Tivenius, is if music is important in itself, it must be difficult to do, but if music is for learning about colours or the days of the week, singing is an appropriate activity because the students are not performing 'real music.…”
Section: Introductionmentioning
confidence: 65%
“…One would therefore assume that singing is an obvious part of everyday life in all ECEC settings. However, mounting evidence suggests that ECEC staff have a considerable lack of confidence in their music-making skills (Barrett et al 2019;Barrett, Flynn, and Welch 2018;Ehrlin 2014;Ehrlin and Tivenius 2018;Ehrlin and Wallerstedt 2014;Flores 2018;Hallam et al 2009;Kim and Kemple 2011;Kulset 2016b;Nardo et al 2006;Russell-Bowie 2009;Stunell 2010;Swain and Bodkin-Allen 2014;Welch and Henley 2014). Barrett et al (2019) found that the more qualified the ECEC staff members were (that is, the more training they had as ECEC teachers), the less favourable their beliefs regarding the role of music in ECEC settings.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan penelitian sebelumnya, menunjukkan bahwa masih sedikit guru yang belum memanfaatkan musik secara maksimal dan mengintegrasikan dalam pembelajaran, khususnya pada kegiatan bermain alat musik. Pada pendidikan anak usia dini, musik lebih banyak digunakan sebagai "latar belakang" kegiatan, dibandingkan kegiatan lain yang bertujuan untuk mengembangkan kreativitas dan keterampilan koginitif dan sosial serta kesejahteraan pada anak di sekolah (Ehrlin, 2018). Adapun beberapa penelitian yang ditemukan, kehadiran musik dalam kegiatan bermain alat musik lebih banyak ditemui dalam penelitian untuk anak berkebutuhan khusus.…”
Section: Pendahuluanunclassified
“…Menurut John yang dikutip oleh Ozmente menjelaskan bahwa pada anak usia dini penting untuk diberikan stimulus dan aktivitas musik untuk dapat mengembangkan perkembangan sosial, kognitif, afektif maupun psikomotorik (Özmente, 2010). Keterbatasan pada proses pembelajaran musik berdasarkan aktivitas yang dilakukan, disebabkan pada kemampuan guru dalam menguasai pendidikan musik (Ehrlin, 2018). Padahal jika ditelusuri lebih lanjut, musik dalam pembelajarannya tidak hanya terbatas pada kegiatan bernyanyi dan mendengarkan lagu.…”
Section: Hasil Dan Pembahasanunclassified
“…Bu noktada okul öncesi öğretmenlerine büyük sorumluluklar düşmektedir. Yapılan birçok araştırmada (Ehrlin ve Tivenius 2018, Garvis ve Pendergast, 2011Hallam ve diğ., 2009;Russell-Bowie, 2009) okul öncesi öğretmenlerinin müzik etkinliklerinde kendilerini yetersiz hissettiklerini ortaya koymaktadır. Öğretmenler öncelikle çocuklara iyi bir model olabilmeli, çocukları motive edebilmeli, müzik etkinliklerini planlayabilmeli, bir çalgı çalabilmeli ve etkinlikleri uygulayabilme becerisine sahip olmalıdır.…”
Section: Sonuç Ve öNeri̇lerunclassified